IMMUNOLOGICAL PROFILE OF SLE PATIENTS WITH ANTIPHOSPHOLIPID ANTIBODY SYNDROME - DR. A. RAVISHANKAR REDDY,; DR. KAMAL CHAND, (International Journal of Pharma and Bio Sciences, 2014)
Studies Associate with APS and SLE are very scanty from our part of country. So the present study was conducted to find out the relation of APS with special reference to SLE in this region. Prospective study was carried out in 103 patients after approval by the Institute Ethical Committee and informed consent was taken from the patients who are attending Kamineni Hospitals. Estimation of different auto-antibodies was done by using standard immunological tests. 103 patients having SLE in the age group 21 to 30 years with female predominance. 22 patients had APS 13 male patients having SLE with APS. The most common clinical manifestation in SLE patients was musculoskeletal involvement (85.18%) followed by fever (74.07%), the patients having SLE with APS musculoskeletal involvement was the most common manifestation (77.27%) followed by fever and mucocutaneous involvement (72.72% and 59.09% respectively). The results are tabulated. APS syndrome is a major cause of morbidity and mortality in patients of SLE. The prevalence of secondary APS syndrome in SLE varies in different geographical regions. The associated complications and its incidence are also variable in different parts of the world because of genetic susceptibility related to aPL and APS. Screening for the presence of aPL antibody and timely initiation of prophylactic treatment can prevent many of complications.